Comparison of Spirometry Values Measured in Healthy Adults with International Standards: (A Case Study of Esfarayen) - Siavash EtemadiNezhad; Khadijeh Gheysar Koushki; Jamshid Yazdani Charati; Seyed Ehsan Samaei (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: One of the most valuable and widely used methods in screening and evaluating respiratory diseases and diagnosing lung disorders is spirometry and comparing its value with standard references. Therefore, the present study aimed to measure and compare spirometric values among adults in Esfarayen (northeastern Iran). Methods: In this cross-sectional study, demographic, anthropometric, and spirometry data (based on American Thoracic Society criteria) were obtained from 317 normal adults in the summer of 2019. Thereafter, the Forced vital capacity  (FVC), forced expiratory volume in 1 s  (FEV1), forced expiratory flow at 25-75% of the pulmonary volume (FEF25-75), and peak expiratory flow (PEF) values in Iranian adult population were compared with predictions from Economic Community for Coal and Steel ( ECCS), Knudson, Morris, and Pereira standardized references Data was analyzed in SPSS (version 18) using descriptive and analytical statistics (Kolmogorov-Smirnov, Pearson correlation and Paired sample t-test). Results: The mean scores of age and Body Mass Index (BMI) of subjects were reported as 29.63±0.38 years and 23.87±0.19 kg/m2, respectively. Statistical analysis demonstrated that the measured values of FVC, FEV1، FEF25-75, and PEF were significantly correlated with Knudson, Morris, ECCS, and Pereira references (P<0.05). Conclusion: The comparison of the measured spirometric values with the international standards revealed that the Morris standard had a very high correlation with all the measured spirometric values. Therefore, this standard was identified as a suitable (consistent) and applicable reference in the study population.